PENGARUH TINGKAT SUKU BUNGA KREDIT DAN CAPITAL ADEQUACY RATIO TERHADAP PROFITABILITAS ( RETURN ON ASSET) (Studi Pada Perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia Periode 2011-2013) - MEDHA AYOE P. TYA; Wiwiek Kusumaning Asmoro (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2014)
The purpose of this research was to determine the effect of financial ratio analysis of the company's profitability in banking. This research is a hypothesis test, which examines the effect of variables that can affect profitability. This research is a quantitative research using secondary data collection techniques, to conduct library research and documentation. The secondary data used in this research were obtained from the official website of the Indonesia Stock Exchange and Bank Indonesia's website. Companies sampled in this research amounted to 15, year of research period from 2011 to 2013, the sampling technique used was purposive sampling. The data used are annual financial statements. Data analysis techniques in this research using multiple regression, hypothesis testing method used is the coefficient of determination, simultaneous regression coefficient test, and test the partial regression coefficients. The results of this research indicate that all information simultaneously Credit Interest Rateand the Capital Adequacy Ratio (CAR), effect on profitability. Partially loan interest rate has no effect on profitability, while the Capital Adequacy Ratio (CAR) that affect profitability.